Exploring Physical Activity in Individuals With Type 2 Diabetes Mellitus and Lower Limb Complications: A Scoping Review - Bingyan Pang; Hannah Porter; Joanne A. McVeigh (Endocrinology, Diabetes & Metabolism)
ABSTRACT Aim To synthesise contemporary evidence on physical activity (PA) levels in people with type two diabetes and lower limb complications (i.e., foot ulcer, peripheral neuropathy [PN], peripheral arterial disease and amputations). Methods A scoping review following the JBI methodology was conducted using six databases: Medline, Embase, PubMed, Cochrane Library, SPORTDiscus and CINAHL. We included observational studies that primarily examined PA (all levels and types) in people with diabetes‐related lower limb complications. Studies published before December 2024 were included. We excluded reviews, intervention studies, and studies that examined the association between PA and T2DM risks. Findings were collated into tables and figures and reported narratively. Results Sixteen studies met the inclusion criteria. Participants were reported to have PN, foot ulcer, peripheral arterial disease, or lower limb amputation. PA was assessed either by questionnaires or activity trackers. PA levels were reported as step count, duration of PA of different intensities, time spent in various postures, gait velocity, step rate and activity score. Mean daily step counts ranged between 1721 (amputation) and 7754 (PN). Mean moderate‐intensity PA was reported to be 2 min per day (amputation) to 37 min per day (PN). Conclusion People living with diabetes‐related lower limb complications engage in low levels of PA. The findings suggest that people with more severe lower limb complications engage in less PA than those with less severe lower limb complications. Future research should standardise PA measurement in individuals with T2DM‐related lower limb complications and use the findings of this review to inform tailored, evidence‐based recommendations.